Technical Assessment Dampak Peledakan pada Bangunan Industri (Studi Kasus Dampak Ledakan Jalan Toll Terhadap Struktur Eksisting) - Indra Komara; Fitri Hardiyanti; Fitria Wahyuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2023)
This paper illustrates the process of blast loading on the structure that is occurring from the work package of Toll Road Construction. The study provides some illustrations including the example of industrial building that is exposed to this load. The aim is to give a technical assessment of the blast loading on the area of the construction. The study is analytically assessed by a numerical modelling created in SAP2000 compared to evaluation of a pressure time history analysis. The result confirms as the initial evaluation that is considering as the behavior after explosion effect.Â Three different load categories classified by the charge mass of TNT, 10 kg, 100 kg and 1000kg are illustrated to accommodate findings and give a recommendation, to undatestand the structural behaviours. As a result, the structure is not collapsing even if the source of the explosion is near. The mass of 1000 kg is considered to destroy some structural elements and it needs to be taken caution for the further analysis.